Who are good and bad citizens? A story-based study with seventh graders - İBRAHİMOĞLU, ZAFER (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
This study primarily aimed to reveal middle-school students' perceptions of citizenship based on their descriptions of good and bad citizens. In this study, meanings that participants attributed to good and the bad citizens were identified and qualitative research methods and techniques were employed. Thirty-four middle-school seventh graders studying at a state school in Istanbul were asked to write a story describing good and bad citizens. The characteristics used by the students in their descriptions were demonstrated as a result of the thematic/content analysis of their stories. The students were found to define citizenship over ethical characteristics related to social life, describe good and the bad citizens based on these criteria, and did not emphasize duties and responsibilities to a large extent. The basic sources behind this perception of citizenship that participants reported were their individual experiences and observations. They stated that they described the characteristics of good and bad citizens per the daily life practices they experienced or observed in their social lives.
Keywords: citizenship education; good citizen; social studies education; PERCEPTIONS; STUDENTS; EDUCATION; TEACHERS